A comparison of two no-arbitrage conditions - Jiang-lun Wu (Frontiers of Mathematics in China, 2014)
We give a comparison of two no-arbitrage conditions for the fundamental theorem of asset pricing. The first condition is named as the no free lunch with vanishing risk condition and the second the no good deal condition. We aim to derive a relationship between these two conditions.